Enhancing students’ creativity in problem-solving through online reading-concept mapping-group investigation - Nur Lina Safitri; Siti Zubaidah; Fatchur Rohman; Sulisetijono Sulisetijono (International Journal of Evaluation and Research in Education (IJERE), 2024)
Enhancement of students’ creativity and problem-solving is essential to science education. The learning accentuating students’ interaction to generate creative ideas becomes the ideal forum for developing those two skills. This study aims to amplify the current understanding of the effects of readingconcept mapping (Remap)–cooperative learning on college students’ creative and problem-solving skills. For cooperative learning, we used group investigation (GI). This study involved 60 college students from three Biology Education classes. Further, each class consists of 20 students with Remap-GI, GI, and conventional learning. The analysis results suggested that the creativity and problem-solving skills of students from all classes increased, with the most significant increase observed in students attending Remap-GI class which also presented substantial differences from the other two classes. In conclusion, GI presents positive effects in enhancing prospective teachers’ skills. However, an additional structured program (Remap) is still required to improve the future teachers’ contribution to their group.